The PTIMIZING THE IMPLEMENTATION OF LEARNING STRATEGIES LIMITED FEATURES TO CLASS V STUDENTS AT SDN 1 BANYUSRI, BOYOLALI REGENCY: PTIMIZING THE IMPLEMENTATION OF LEARNING STRATEGIES LIMITED FEATURES TO CLASS V STUDENTS AT SDN 1 BANYUSRI, BOYOLALI REGENCY - siti (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
ABSTRACTThe author performs the actualization and habituation with the aim of applying the basic values ​​of civil servants (BerAKHLAK) namely Service Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive and Collaborative. In addition, it is to implement the position and role of civil servants to support the realization of Smart Governance, namely Management ASN and SMART ASN. This actualization activity is carried out from April 9 to June 8, 2022 by applying the basic values ​​of civil servants, including Service Oriented, Accountable, Harmonious, Loyal, Adaptive and Collaborative as well as carrying out activities based on the position and role of civil servants, including Management ASN and SMART ASN.The actualization and habituation activity with the title: "Optimizing the Implementation of Limited Face-to-Face Learning Strategies for Class V Students at SDN 1 Banyusri, Boyolali Regency" was carried out based on the results of the actualization for one month to implement the values ​​of AKHLAK through activities 1) Implement the SAPI program KUAT (I'm Sure I Can Breakfast) video playback using the LCD 2) Carry out Story Telling 3) Implement GAMEBEJAR 4) Make building props 5) Carry out QUIZIku activities 6) Evaluate actualization activities.From the activities carried out by the author, it can be concluded that the actualization and habituation activities are carried out by optimizing the learning model using the PBL (Problem Based Learning) model so as to increase the enthusiasm of students' learning activities so as to make students enthusiastic about learning and increase student learning outcomes. Thus, the above provides benefits in choosing a learning model for the material to carry out story telling more safely so that students can easily understand the material in learning using PBL so that students are more active. Keywords: Actualization and Habituation of Basic Moral Values, Learning Strategies